Condylar re-positioning devices in orthognathic surgery - is there a benefit to their use? - R. Leader; O. Carty (Elsevier, 2023)
The bilateral sagittal split osteotomy (BSSO) is the established workhorse in mandibular orthognathic surgery. Despite the frequency at which this procedure is performed, alterations in condylar position from the surgery remain a concern to the operating surgeon. Such changes in condylar positioning have long been associated with relapse. A systematic literature review was carried out to address the question: 'condylar re-positioning devices in orthognathic surgery - is there a benefit to their use?'. As of yet there is no robust scientific evidence to suggest that these devices confer any clinical benefit over traditional manual re-positioning in orthognathic surgery cases. It would seem appropriate that future research focus on cost effective methods for intra-operative identification of a mal-positioned condyle with the aim of preventing later relapse.